3D‐Printing of Poly(arylene ether sulfone)s: Functional High‐Performance Polymers for Vat Photopolymerization. Issue 1 (11th October 2022) - Weyhrich, Cody W.; Will, John W.; Heifferon, Katherine V.; Brown, James R.; Arrington, Clay B.; Meenakshisundaram, Viswanath; Williams, Christopher B.; Long, Timothy E.
Abstract: Vat photopolymerization (VP) is an advanced additive manufacturing (AM) platform that enables production of intricate 3D monoliths that are unattainable with conventional manufacturing methods. In this work, modification of amorphous poly(arylene ether sulfone)s (PSU) allows for VP printing. Post‐polymerization telechelic functionalization with acrylate functionality yielded photocrosslinkable PSUs across a molecular weight range. 1 H NMR spectroscopy confirms chemical composition and quantitative acrylate functionalization. Addition of diphenyl‐(2, 4, 6‐trimethylbenzoyl)phosphine oxide (TPO) photoinitiator to 30 wt% PSU solutions in NMP provides a photocurable composition. However, subsequent photorheological studies elucidate rapid photodegradation of the polysulfone main chain, which is especially apparent in high M n (15 kg mol −1 ) PSU formulations. UV‐light intensity and wavelength range are altered to reduce degradation while allowing for efficient crosslinking. The addition of 0.5 wt% of avobenzone photoblocker produces an ill‐defined structure with 6 kg mol −1 PSU. For higher molecular weights (>12 kg mol −1 ), solutions with a low molar mass reactive diluent, i.e., trimethylolpropane triacrylate, enable the printing of an organogel with a storage modulus (>10 5  Pa) sufficient for vat photopolymerization. Employing multicomponent solutions provide well‐defined parts with complex geometries through vat photopolymerization. Abstract : Poly(arylene ether sulfone)s are amorphous high‐performance polymers, which display excellent thermomechanical properties. However, their inherent photo instability prohibits use in UV‐assisted additive manufacturing methods. Control of UV wavelength, intensity, and photosensitivity of the polysulfone solutions enables vat photopolymerization of this polymer family for the first time with complex parts showcasing high resolution prints.